COMPUTER-ASSISTED STRUCTURE ELUCIDATION OF HUMULENE EPOXIDE AND CARYOPHYLLENE EPOXIDE MIXTURE OF TURRAEA BROWNII - Tahid Tahid; J. D. Connolly (Research Center for Chemistry - LIPI, 1994)
An experiment was carried out to isolate active material from Turraea brownli for biological insectislde. The isolated component obtained by using TLC was elucidated with iH NMR, and 13C NMR techniques. It was found that the compound was unknown triterpenoid (C30H48O). Further elucidation using 2D NMR with COSY, HMBC, and HMQC combined with computer techniques showed that the component was an approximately equimolar mixture of two sesqulterpenes (C15H24O) which were identified as humulene epoxide and B-caryophyllene epoxide.